The impact of metabolic overweight/obesity phenotypes on unplanned readmission risk in patients with COPD: a retrospective cohort study - Tian, Yang; Liu, Luna; Li, Yuchen; Fan, Xiude; Wu, Wanhong; Shi, Yingzhou; Jiang, Jie; Yuan, Zinuo; Dong, Hang; Li, Huijie; Xuan, Qiuhui; Xu, Chao (Frontiers in Physiology, 2023)
Background: There is an inconsistent association between overweight/obesity and chronic obstructive pulmonary disease (COPD). Considering that different metabolic characteristics exist among individuals in the same body mass index (BMI) category, the classification of overweight/obesity based on metabolic status may facilitate the risk assessment of COPD.Our study aimed to explore the relationship between metabolic overweight/obesity phenotypes and unplanned readmission in patients with COPD.We conducted a retrospective cohort study using the Nationwide Readmissions Database (NRD). According to metabolic overweight/obesity phenotypes, patients were classified into four groups: metabolically healthy non-overweight/obesity (MHNO), metabolically unhealthy non-overweight/obesity (MUNO), metabolically healthy with overweight/obesity (MHO), and metabolically unhealthy with overweight/obesity (MUO).The primary outcome was unplanned readmission to hospital within 30 days of discharge from index hospitalization. Secondary outcomes included in-hospital mortality, length of stay (LOS) and total charges of readmission within 30 days.Results: Among 1,445,890 patients admitted with COPD, 167,156 individuals were unplanned readmitted within 30 days. Patients with the phenotype MUNO (hazard ratio [HR], 1.049; 95%CI, 1.038-1.061; P < 0.001) and MUO (HR, 1.061; 95%CI, 1.045-1.077; P < 0.001) had a higher readmission risk compared with patients with MHNO. But in elders ( ≥ 65yr), MHO also had a higher readmission risk (HR, 1.032; 95%CI, 1.002-1.063; P=0.039).Besides, the readmission risk of COPD patients with hyperglycemia or hypertension regardless of overweight/obesity increased (P < 0.001).In patients with COPD, overweight/obesity alone had little effect on unplanned readmission, whereas metabolic abnormalities regardless of overweight/obesity were associated with an increased risk of unplanned readmission. Among the metabolic abnormalities, particular attention should be paid to hyperglycemia and hypertension. But in 3 elders (≥65yr) overweight/obesity and metabolic abnormalities independently exacerbated the adverse outcomes.